The Influence of Teachers' Pedagogical Competence on the Implementation of Differentiated Instruction at Muhammadiyah Senior High School Imogiri - Wulandari, Fitria; Sudrajat (JIPSINDO, 2025)
This research is motivated by the implementation of the Independent Curriculum which requires the creation of a flexible and student-centered learning approach. Teacher competence in carrying out differentiated learning is an important component for achieving a maximum educational process. This research seeks to examine the extent to which teachers’ pedagogical competence affects the application of differentiated instruction at Muhammadiyah Senior High School Imogiri. This research employs a descriptive quantitative approach. The data were analyzed using several techniques, including tests for validity, reliability, and normality, as well as simple linear correlation and regression analysis. The subjects in this study amounted to 22 teachers with the main instrument in the form of questionnaires. The findings indicate that teachers’ pedagogical competence exerts a positive and significant impact on the implementation of differentiated instruction at SMA Muhammadiyah Imogiri. This is supported by the regression analysis results, which indicate that teachers’ pedagogical competence accounts for 54.4% of the effectiveness in implementing differentiated learning. These findings also show that aspects such as understanding student characteristics, selecting appropriate learning methods, and being able to design adaptive learning are important factors. Teachers with higher levels of pedagogic competence tend to be able to build a responsive, inclusive, and student-oriented learning environment. Therefore, enhancing pedagogical competence is a strategic effort to support the successful enactment of the Independent Curriculum within schools.